Kinetic study of hydromagnesite thermolysis by constant rate thermal analysis - DIOUANI, Jaouher; Nahdi, Kaïs (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The present work is focused on the kinetic study of hydromagnesite thermal decomposition carried out by constant rate thermal analysis technique at 5 hPa partial pressure. The apparent activation energies were measured experimentally all along the decomposition without any assumption about the rate law of the determining step. Under these conditions the decomposition of hydromagnesite occurs in two steps. The first step is a dehydration which occurs with apparent activation energy of 60 kJ.mol-1 and D4 kinetic model. The second step is essentially decarbonatation, which occurs according to an F1 kinetic model and activation energy equal to 95 kJ.mol-1.Â 